The Critical Enabler: How 5G Networks are Revolutionizing Real-Time Telemedicine - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The convergence of telecommunications and healthcare is ushering in a new era of medical service delivery: telemedicine. While earlier network generations la...
Keywords: Digital Health; Diagnostics; Healthcare Innovation; Medical Ethics; Patient Care